Pengaruh Iklim Organisasi Terhadap Kinerja Karyawan - Nuryasmin, Rt Nindica Azalea; Chaniago, Harmon (POLITEKNIK NEGERI BANDUNG, 2016)
Creating a climate of an organization capable of bringing the employees in a company to create a high performance is not an easy thing. This is because basically, humans have different characteristics according to his needs. Although those cases, human resources should have a good performance. One way to improve the performance of employees is to pay attention to organizational climate. This study aims to determine the organizational climate on employee performance office of PT Ultrajaya Milk Industry and Trading Company. Organizational climate measurements include the dimensions of the structure, standards, support, recognition, responsibility, and commitment. While the measurement of employee performance using the dimensions of the work, work behavior, and personal qualities. The study uses quantitative methods and involved 126 respondents drawn from employees of the office. Data was collected by questionnaire were then analyzed using descriptive statistics. The analysis includes the analysis of assumptions used classic, descriptive analysis, correlation analysis, regression analysis and coefficient of determination. Based on the research results, the level of organization climate is in the category of